Maternal and Newborn Health Care Practices in Rural Bangladesh - Ansari, Md Mostaque Hossain; Biswas, Sailendra Nath; Hussain, Rubaiyat Farzana; Ripon, Shariful Hasan; Hossain, M Nazmul (KYAMC Journal, 2017)
Maternal and child health indicators have improved in Bangladesh but still pregnancy and child birth related complications are the leading causes of death of mother and children. Practices associated with these mortality reductions are not followed similarly throughout the country. This descriptive study was carried out to examine the prevalence of maternal and newborn-care practices in the rural area of Bangladesh. Face to face interview was conducted to collect data using closed end questionnaire from the purposively selected 589 women of reproductive age having at least one child. SPSS version 16 software was used for computation and analysis of data. Among the respondents, 58.4% received ANC visits but only 32.3% had completed minimum required visits ( 3). Effective immunization of mothers against tetanus was 93.3%. Home delivery incidence was 72.3 % and 92.2% of all deliveries were attended by trained health professionals. Only 17.0% got PNC visits. Birth weight recording coverage was only 34.5%. Maternal and newborn health care practices could not be eulogized for low coverage of ANC, PNC, birth weight recording and high incidence of home delivery. Recommendations were made to improve the quality of MCH service and service providers and to strengthen the motivational program for community participation. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 453-457